Internal auditing - Bigg, Walter W.; Davies, John Ogwen (London : The stellar press, 1965)
This books throw light on modern internal auditing. The book further highlights tricks and strategies for conducting internal audit.
Includes index
asm 21/01/19
Loans
Keywords: Auditing